Alexander von Humboldt’s Images of Landscape and the ‘Chaos of the Poets’ - Clark, Rex (HiN - Alexander von Humboldt im Netz. Revue internationale d’études humboldtiennes, 2005)
Abstract Alexander von Humboldt’s descriptions of volcanic mountains in his travel journals (Reise auf dem Río Magdalena, durch die Anden und Mexico) show both his reliance on and impatience with literary conventions and travel narratives. Using Goethe’s „Italienische Reise“ and Bürger’s „Münchhausen“ as points of comparison for literary treatments of the volcano ascent, Humboldt’s process of writing is examined. Humboldt shows the failure of the existing discourse and begins to experiment with narratives which fragment and recombine personal and historical modes of writing with, in this case, images from new technical inventions which visualize landscape according to fundamental scientific principles. While the inclusion of scientific prose is relevant, Humboldt’s link to modernity is based on experimental narrative techniques which draw upon changing sets of discourse practices to describe complex realities. Zusammenfassung Alexander von Humboldts Beschreibungen von Vulkanen in seinen Reiseberichten (Reise auf dem Río Magdalena, durch die Anden und Mexico) zeigen sowohl das Zutrauen zu als auch die Ungeduld mit literarischen Konventionen und Reiseerzählungen. Indem Goethes „Italienische Reise“ und Bürgers „Münchhausen“ als Vergleichsstoffe für literarische Darstellungen der Vulkanbesteigung herangezogen werden, untersucht der Aufsatz Humboldts Schreibprozeß, um moderne Formen von Abbildung und Metapher zu finden. Resumen Las descripciones de Alexander von Humboldt de las cadenas montañosas de formación volcánica en su relación de viaje evidencian tanto confianza como impaciencia con respecto a los relaciones de viaje de otros cronistas tomados como modelos literarios. En la comparación con “El viaje italiano“, de Goethe, y con “Münchhausen“, de Bürger, como ejemplos literarios de ascensiones a volcanes, se analiza el proceso de escritura de Humboldt para buscar formas modernas de ilustración y metáfora.